An evaluation of a comprehensive training package for interventionists providing behavioral intervention for children with autism spectrum disorder. (29th September 2020) - Cheung, Yvonne; Man Kit Cheung, Ambrose; Ho Yan Luk, Eunice; Man Fung, Yiu; Mountjoy, Toby; Cihon, Joseph H.; Leaf, Justin B.
Abstract : There has been rapid growth in the number of behavior analysts and interventionists in the world today. With this growth it is imperative to ensure that each behavior analyst and interventionist receives quality training. The training should be comprehensive (i.e. training multiple areas of behavior analysis) and should not conclude until the trainee is able to perform each behavior analytic procedure to a high degree of fidelity. The purpose of this study was to evaluate the effectiveness of a training package to train four participants how to implement multiple behavior analytic procedures. Using a multiple baseline design across participants the results indicate that each participant improved their implementation of behavioral intervention. Additionally, the participants maintained their skills over time.